Rethinking the implementation of the revised history curriculum: teachers` and learners` preparedness in selected public secondary schools in Khomas region, Namibia - Mothowanaga, Ndinelao N.; Gladwin, Bhebhe (Namibian Journal for Research, Science and Technology, 2022)
The objective of the study is to determine the preparedness of both teachers and learners in implementing the revised History curriculum in secondary schools (grade 8-12) since the introduction of the revised curriculum in 2017. Jess, Carse, and Keay (2016) discovered that teachers must be prepared and trained in order to accomplish the objectives of a curriculum; the authors’ attention was on the curriculum-development process and the educator’s role. Teachers are familiar with classroom circumstances and may be able to identify gaps and implement changes and enhancements that will assist students in achieving the desired results. Furthermore, teachers must be able to provide developmentally appropriate learning challenges that are connected with curricular requirements. The focus of training and professional development must be on teaching students how to appropriately interpret the curriculum so that their needs are met through suitable instructional approaches. Allowing teachers main engagement in curriculum development and the process of alignment as it relates to identifying student needs and then instructing accordingly, as recommended by Jess et al. (2016), is one method to assist this situation. Learners are also a crucial component in curriculum implementation. While teachers are the ones who decide what happens in the classroom, it is the learners who decide what is actually communicated and adopted from the official curriculum. Unprepared teachers and learners are impediment to the effectively implementation of curriculum processes. The lack of preparedness among teachers, as well as their attitudes and morale, has a negative impact on the implementation of the curriculum therefore, proper training should be provided to teachers in order to prepare them in all aspects of the curriculum in order to enhance their ability to deliver and implement the curriculum effectively. The study recommends that teachers need have proper training before they implement the new or revised curriculum. It is also recommended that NIED in collaboration with the ministry of education be holding regular training and workshops for teachers and to have a follow-up system in place to ensure that the trainings are effective. This will aid teachers in understanding the varied expectations of the new curriculum as well as staying current or abreast to current curricular changes.